Selective Emergence of the Halogen Bond in Ground and Excited States of Noble‐Gas–Chlorine Systems. (20th February 2019) - Pirani, Fernando; Cappelletti, David; Falcinelli, Stefano; Cesario, Diego; Nunzi, Francesca; Belpassi, Leonardo; Tarantelli, Francesco
Abstract: Molecular‐beam scattering experiments and theoretical calculations prove the nature, strength, and selectivity of the halogen bonds (XB) in the interaction of halogen molecules with the series of noble gas (Ng) atoms. The XB, accompanied by charge transfer from the Ng to the halogen, is shown to take place in, and measurably stabilize, the collinear conformation of the adducts, which thus becomes (in contrast to what happens for other Ng‐molecule systems) approximately as bound as the T‐shaped form. It is also shown how and why XB is inhibited when the halogen molecule is in the 3 Πu excited state. A general potential formulation fitting the experimental observables, based on few physically essential parameters, is proposed to describe the interaction accurately and is validated by ab initio computations. Abstract : Die intermolekulare Wechselwirkung in Edelgasaddukten mit Cl2 zeigt spezielle Merkmale beim Vergleich mit diatomaren Molekülen. So liegt, zusammen mit einem beträchtlichen Ladungstransfer vom Edelgas zu Cl2, für die kollineare Konformation mit Cl2 in dessen Grundzustand eine Halogenbrücken‐Beteiligung vor und stabilisiert das Konformer. Die Halogenbrücke ist inhibiert, wenn sich Cl2 in seinem angeregten Zustand befindet.